Smartphones From an Applied Research Perspective 2017
DOI: 10.5772/intechopen.70284
|View full text |Cite
|
Sign up to set email alerts
|

Examining Merchants’ Refusal to Adopt Mobile Payment Systems in Spain

Abstract: Over the past years, traditional company management has been undergoing major changes regarding the adoption, implementation, and development of new technologies. Even if Internet commerce has the potential to revolutionize consumer behavior and the way merchants communicate with their customers, it is true that several activities related to the new technologies are still in the early stages of development or implementation. The main purpose of this study is to assess the determinants of m-payments from the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Based on the review of previous literature, we found some studies that could help us understand more about mobile payment in the context of the organization. Overall, the papers relating to firms and merchants discuss three different objectives: to investigate factors influencing merchant’s adoption (Apanasevic et al , 2016; Guo and Bouwman, 2016; Hayashi and Bradford, 2014; Khan and Ali, 2018; Lai, 2012; Liébana-Cabanillas et al , 2017; Nguyen and Lu, 2018; Nyawo, 2017; Otieno and Kahonge, 2014; Van der Heijden, 2002); to explore the drivers and barriers that hinder the mobile payment acceptance (Apanasevic, 2013; Liébana Cabanillas et al , 2016; Mallat and Tuunainen, 2005; Mallat and Tuunainen, 2008; Petrova and Wang, 2013; Schuster et al , 2016); and to understand the impact of mobile payment on business growth (Amegbe et al , 2017; Bosire and Ntale, 2018; Chale and Mbamba, 2015; Mbogo, 2010; Nyaga, 2013; Tumaini, 2016). …”
Section: Literature Review Background Theory and Hypotheses Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the review of previous literature, we found some studies that could help us understand more about mobile payment in the context of the organization. Overall, the papers relating to firms and merchants discuss three different objectives: to investigate factors influencing merchant’s adoption (Apanasevic et al , 2016; Guo and Bouwman, 2016; Hayashi and Bradford, 2014; Khan and Ali, 2018; Lai, 2012; Liébana-Cabanillas et al , 2017; Nguyen and Lu, 2018; Nyawo, 2017; Otieno and Kahonge, 2014; Van der Heijden, 2002); to explore the drivers and barriers that hinder the mobile payment acceptance (Apanasevic, 2013; Liébana Cabanillas et al , 2016; Mallat and Tuunainen, 2005; Mallat and Tuunainen, 2008; Petrova and Wang, 2013; Schuster et al , 2016); and to understand the impact of mobile payment on business growth (Amegbe et al , 2017; Bosire and Ntale, 2018; Chale and Mbamba, 2015; Mbogo, 2010; Nyaga, 2013; Tumaini, 2016). …”
Section: Literature Review Background Theory and Hypotheses Formulationmentioning
confidence: 99%
“…to investigate factors influencing merchant’s adoption (Apanasevic et al , 2016; Guo and Bouwman, 2016; Hayashi and Bradford, 2014; Khan and Ali, 2018; Lai, 2012; Liébana-Cabanillas et al , 2017; Nguyen and Lu, 2018; Nyawo, 2017; Otieno and Kahonge, 2014; Van der Heijden, 2002);…”
Section: Literature Review Background Theory and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extent literature indicates that the consumer's perception of risk is the most significant deterrent of the much-anticipated rise in the adoption of mobile payments (Taylor, 2016;Pelaez et al, 2017;Park et al, 2018;Killian and Kabanda, 2020). Analogous to these previous findings, of the 56 scientific articles reviewed by by Liébana-Cabanillas et al (2017) between 2002.63% of them identified perceived risk as the main barrier to the adoption of mobile payments, yet understanding remain fragmented for several reasons. First, Pelaez et al (2017) and Park et al (2018) identify perceived risk as a unidimensional construct while Groß (2016) and Yang et al (2016) consider it multi-dimensional to suggest inconsistencies in literature that require further research.…”
Section: Introductionmentioning
confidence: 59%
“…(Abhishek and Hemchand, 2016;Madan and Yadav, 2016). Meanwhile, from the merchant side, they have more attention on the technical and functional aspects of a service that is based on technology (Cabanillas et al, 2016, Cabanillas et al, 2017Li, 2018)…”
Section: Intention To Usementioning
confidence: 99%